Spatial distribution and tectonic significance of the landslides triggered by the 2021 Ms6.4 Yangbi earthquake, Yunnan, China - He, Xiangli; Xu, Chong (Frontiers in Earth Science, 2022)
An Ms6.4 earthquake occurred on 21 May, 2021 in Yangbi County, Yunnan Province, located in the strong earthquake hazard zone, the border of the Sichuan-Yunnan rhomb block, southeast Tibetan Plateau, causing severe loss of life and property. Adequate research on the distribution characteristics and seismotectonic mechanisms of seismic chain-generated hazards in the region is meaningful for mitigating seismic hazard risks. In this paper, based on the interpretation of remote sensing satellite images and the analysis on GeoScene platform, we compile a detailed inventory of landslides induced by the Yangbi earthquake and analyze the correlation of their spatial distribution with the influence factors. The results show that 95 landslides were interpreted, and their spatial distribution is correlated to the topographic, seismic and geological factors. Statistically, the landslide number and mobility increase with the slope angle; the south- and southeast-facing slopes and weaker metamorphic rocks are more prone to landslides; the higher the seismic intensity, the larger the density and scale of landslides. Furthermore, the development of the landslides is not only influenced by the Ms6.4 mainshock, but also by the Ms5.6 foreshock, which is significantly correlated with the size of landslides. Notably, the long axis of the landslide distribution area is in NW-SE direction, which is nearly parallel to the strike of the Weixi-Qiaohou-Weishan fault zone (WQWF). The landslides are mainly distributed in the southwest wall and southeast section of the fault. The landslide number and density unstably decrease with the vertical distance from the fault with many fluctuations. Combined with the previous studies, two possible seismogenic structure models are inferred. One model is a parallel secondary fault of the WQWF, Another one is a flower structure in the southwest wall of the WQWF. Both models are mainly characterized by right-lateral strike slip with a small normal-fault component. Additionally, the seismic rupture propagated mainly to the southeast along the seismogenic fault in the subsurface without surface rupture.